Analisis Kesalahan Siswa Berdasarkan Prosedur Newman dalam Menyelesaikan Soal Sistem Persamaan Linier Dua Variabel ditinjau dari Gaya Kognitif - Virnia, Virnia Dwi Rahmawati; Fadillah, Syarifah; Astuti, Reni (Indo-MathEdu Intellectuals Journal, 2025)
This research is a qualitative descriptive research. This study aims to analyze students' errors in solving SPLDV problems based on the Newman procedure in terms of cognitive style. This research was conducted at SMP Negeri 1 Sandai with the research subjects being grade VIII students. Then two students were taken each based on the Field Dependent cognitive style and the Field Independent cognitive style to be interviewed. The data analysis technique used in this study is the description method. Some of the results of the analysis of student errors in the Newman procedure, obtained a percentage of errors in understanding the questions 76%, transformation 50%, process skills 23%, and writing the final answer 90%. Based on the overall results of the percentage of student errors, it was found that students with the Field Dependent cognitive style made more mistakes than Field Independent students with the overall percentage of the Newman procedure in terms of student cognitive style. 36% errors in understanding the questions, 23% transformation errors, 3% process skills, and 38% writing the final answer.